2018
DOI: 10.12659/msm.906867
|View full text |Cite
|
Sign up to set email alerts
|

Basic Parameters of Blood Count, Serum Sodium, and Creatinine as Prognostic Factors for Renal Cell Carcinoma at Five-Year Follow-Up

Abstract: BackgroundSeveral nomograms were developed for predicting the potential recurrence and cancer death risk in renal cell carcinoma patients. The combination of TNM classification and appropriately selected clinical classifiers allows for the creation of simple and effective risk calculators.Material/MethodsThere were 230 patients with renal cell cancer enrolled in this study. Basic parameters of blood count, serum creatinine and sodium concentrations, and histopathological features of the tumors were analyzed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Although biomarkers associated with OS in patients with CRC may be moderately predictive of survival, additional research and evaluation are needed to improve their predictive utility (18)(19)(20)(21). In this study, we evaluated association between Scr levels and OS in patients with CRC because Scr has been reported to be predictive of prognosis in many cancers (8)(9)(10)(11). Our study revealed a correlation between Scr concentrations and OS in patients with CRC, which was consistent with previous studies in other cancers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although biomarkers associated with OS in patients with CRC may be moderately predictive of survival, additional research and evaluation are needed to improve their predictive utility (18)(19)(20)(21). In this study, we evaluated association between Scr levels and OS in patients with CRC because Scr has been reported to be predictive of prognosis in many cancers (8)(9)(10)(11). Our study revealed a correlation between Scr concentrations and OS in patients with CRC, which was consistent with previous studies in other cancers.…”
Section: Discussionsupporting
confidence: 88%
“…In a retrospective cohort study, Scr was an independent predictor of overall survival (OS) in 498 patients with primary epithelial ovarian cancer (9). Z ̇yczkowski et al found that Scr may be useful for estimating the 5-year survival of patients with renal cell carcinoma (10). Similarly, Panotopoulos et al found that Scr was highly associated with disease-specific survival in 84 patients with liposarcoma (11).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytosis had been found as a worse prognostic predictor in different kind of cancer, include nasopharyngeal carcinoma [20], gynecologic malignancies [21], melanoma [22] and colorectal cancer [23].In RCC, thrombocytosis also could be regard as a prognostic indicator. Several study had already shown patients with preoperative thrombocytosis had a worse survival than those who without [24][25][26].Although none of these study had con rmed the thrombocytosis had worse prognosis in population of RCC with TT, previous study had found that bland thrombus in RCC with TT was associated with adverse survival [27]. Combine with our study, patients with thrombocytosis had an increased recurrence or metastasis risk than those who without.…”
Section: Discussionsupporting
confidence: 77%
“…In RCC too, thrombocytosis could be regarded as a potential prognostic indicator. Several studies have shown that patients with preoperative thrombocytosis had worse survival than those without it [ 24 – 26 ]. Although none of the studies linked thrombocytosis to worse prognosis in RCC population with TT, a study found that bland thrombus in RCC with TT is linked to adverse survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%